The Role Of Teachers In School And Community - Zainal Arifin (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
This study aims to discuss the role of teachers in schools and society. This research is a qualitative research with the type of library research, and the data analysis techniques are using inductive and deductive methods. The findings of this study can be concluded: first, in schools, the role of the teacher is to create educational interactions that educate students. Teachers are required to be able to show authority or authority, meaning that they must be able to control, regulate and control children's behavior. If necessary he can use his power to force the child to study, do his job or obey the rules. With authority he enforces discipline for the smooth and orderly teaching-learning process. Compassion absolutely must be possessed by a teacher. If the teacher does not have authority, he will have difficulty guiding his students to comply with the rules for the sake of orderliness in school to support the success of the teaching and learning process. Second, in the community the teacher can play many roles, namely: (a) the teacher as a teacher; (b) teachers as educators; (c) teachers as role models; and (d) the teacher as a motivator.